Populism as a Communication Strategy: A Case Study of the Freedom and Direct Democracy Party and Tomio Okamura - Charvát, Jakub; Charvátová, Denisa; Niklesová, Eva (Communication Today, 2022)
Democratic systems face several challenges, many of which are based on current societal sentiments. Western societies may enjoy life in prosperity but many of their citizens are dissatisfied as they live in fear of the future. While the established political parties are unable to respond effectively, populist parties work effectively with fear. Thus, populism has been on the rise. Although populism appears in the communication of parties at both ends of the left-right axis, in most cases it is associated with the extreme right. A key element in the success of populist parties is their communication strategy while social media have become an ideal platform for populist political communication. The single-country case study focuses on Czech politics, in which this area was occupied by the Freedom and Direct Democracy Party, led by Tomio Okamura. The study analyses the political communication of the party and of Okamura, especially its content and form.